The Influence of Education and Training (Diklat) and Discipline on the Performance of Members of Polda Metro Jaya - Muhammad Yudha Prihantoro; Zaharuddin; Dudun Junaedi (Journal Informatic, Education and Management (JIEM), 2026)
This research aims to determine the influence of education and training (diklat) and discipline on the performance of members of Polda Metro Jaya. Police member performance is an important factor in maintaining the effectiveness of public services and community security. The method used in this research is quantitative with descriptive and verificative approaches. Data collection was conducted through questionnaire distribution to 96 respondents who are members of Polda Metro Jaya. The results show that education and training (diklat) has a positive influence on member performance with a contribution of 48.9%. Discipline also provides a positive influence with a larger contribution, namely 63.9%. Simultaneously, education and training (diklat) and discipline together have a significant influence on member performance of 67.2%. Therefore, it can be concluded that improving education and training (diklat) as well as consistent enforcement of discipline can optimally enhance the performance of members of Polda Metro Jaya.